Farmer identities influence wildlife habitat management in the US Corn Belt. Issue 1 (29th October 2021) - Dixon, Adam P.; Arbuckle, J. Gordon; Ellis, Erle C.
Abstract: Farmer wildlife management practices are critical to conserve biodiversity and ecosystem functions across intensively used agricultural landscapes. Policies and initiatives aimed at encouraging these practices have generally focused on economic incentives, with limited effectiveness. Farmer identity theory addresses the emergence of norms, values and perceptions in farm management and can contribute to the development of policies and initiatives that engage more effectively with farmers and farming communities. Here we evaluate linkages between farmer identity and wildlife habitat management practices in the intensively farmed US state of Iowa. We conducted an exploratory factor analysis using data from a survey of over 1, 300 Iowa farmers that asked their opinions on what constitutes 'a good farmer'. We use logistic regression to model relationships between farmer identity factor scores and contextual variables against participation in a set of habitat management practices. Four 'good farmer' identity types were identified and labelled as productivist, soil conservationist, wildlife conservationist and civic‐minded. Logistic regression results indicated that these farmer identity types have highly divergent responses to wildlife habitat management practices among Iowa farmers. Recreational factors may supplement identity and are also influential towards habitat production on farms. We conclude that farmer identity theory offers a critical link between social and ecological processes on Iowa farms. The research presented here quantitatively associates farmer identity theory with wildlife habitat management, increasing our understanding of how wildlife habitat practices and individual‐level farmer identities interact. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.